Aerobic motor skills and the effectiveness of football players on the example of German Club BSC Eintracht Südring Berlin - Paweł Kalinowski; Katarzyna Kalinowska; Monika Nowakowska; Andrzej Wieczorek; Damian Jerszyński (Nicolaus Copernicus University in Toruń, 2019)
Constant development and commercialization of football makes it somewhat compelling to look for proven solutions in order to determine both the represented players' level of competence and the most important components of the effectiveness or efficiency of a game. Evolution of walking distance over the years directs attention towards the aerobic motor skills. In this report, there have been made attempts to determine the relationship between the effectiveness of the game and the endurance of the tested football players of the BSC Eintracht Südring Berlin club. The research covered a group of 22 players from the Berlin club. The tests were carried out in the autumn round of the 2018/2019 season in Berlin in the period from July to November 2018. The endurance was measured with the help of the Cooper Test, while the players' performance was evaluated by the method of competent judges. The results of the study were statistically analyzed in the Statistica 13.1 program. Descriptive statistics were carried out, the minimum (min), maximum (max), average (X) and standard deviation (SD) values were calculated, and the coefficient correlation was determined. It was noted a significant correlation between the effectiveness of the game and the endurance.